Imajinasi Anak Saat Bermain dalam Lukisan Kontemporer - Alyssa Khoirunnisa Supriyanto; Yasrul Sami (Journal on Education, 2024)
The purpose of this final work is to visualize the form of child imagination when they are playing into contemporary art. In its creation, this artwork visualize the ambiance and what the child imagine when they are playing with their toys or simple things around them. The method in this artwork creation consist of five stages : (1) Preparation, (2) Elaboration, (3) Synthesis, (4) Concept Realization, and (5) Finishing. There are ten artworks that have gone through the art creation process are “Hewan-Hewan di Langit”, “Pesta Teh dan Kue”, “Istana Selimut”, “Sang Penyelamat”, “Seniman Kecil”, “Bertarung”, “Menghindari Lava”, “Belayar Kapalku”, “Aku Melayang”, and “Koki Cilik”.